Improved prevention of female genital schistosomiasis: piloting integration of services into the national health system in Côte d’Ivoire - Preston, Ashley; Vitolas, Carlos Torres; Kouamin, Alain Claver; Nadri, Johara; Lavry, Suzanne Lobohon; Dhanani, Neerav; Dje, Norbert; Toh, Alain; Fleming, Fiona M.; Meite, Aboulaye (Frontiers in Tropical Diseases, 2023)
Introduction Female genital schistosomiasis (FGS) is a neglected gynecological condition, putting women at-risk of poor sexual and reproductive health (SRH), including pregnancy complications or infertility. Early treatment of schistosomiasis with praziquantel is important to avoid disease progression to FGS as it is not always possible to reverse these symptoms. However, prevention programs with praziquantel have historically focused on school-aged children. Therefore, there is a gap to provide prevention services for young women in endemic areas, including Côte d’Ivoire. Methods We piloted integration of FGS prevention services into routine SRH care in seven health centers (Soubré district, Côte d’Ivoire, November 2020 to April 2021) and enrolled 56 health workers. We used mixed methods including key informant interviews, focus group discussions, and questionnaires to determine effectiveness, feasibility and acceptability of integration across health system decision makers, health workers and female patients (15 to 29 years old). For qualitative data, we used an inductive coding process to analyze themes. We used descriptive statistics to analyze quantitative data. Results Interviewed health workers perceived that the integrated services increased access and improved health outcomes for women (15 to 29 years old) due to the more comprehensive approach, although barriers to access included lack of transportation. Female patients surveyed at baseline (n=448) indicated there were no routine FGS prevention services. During the pilot, FGS prevention services were provided to >8500 women at-risk. Health workers interviewed at the end of the pilot indicated they could feasibly provide FGS prevention services as part of routine patient consultations, and they maintained knowledge from training on the key FGS health education points and the consultation processes to follow. The greatest challenge expressed by health workers was the high workload. Discussion Provision of integrated healthcare in the health center setting is an effective and acceptable way to increase access to prevention services and provide holistic care for women (15 to 29 years old) in this setting in Côte d’Ivoire. Future scale-up will require further streamlining of the strategy, building on existing platforms, whilst ensuring reduced impact on workload and consideration of how to overcome barriers to accessing health centers.